PROFIL LIPID WANITA MENOPAUSE DI PANTI WERDHA DAMAI MANADO - Sumoked, Prisilia D. D.; Tendean, Hermie M. M.; Suparman, Eddy (e-CliniC, 2016)
Abstract: In Indonesia, women over the age of 50 years that will become menopause in 2020 are estimated as many as 30.3 million people. A decline in estrogen level at menopause will affect the functions of the female reproductive system as well as of the other body systems, including lipid metabolism. This study was aimed to determine the lipid profile of menopausal women at Panti Werdha Damai (senior housing) Manado. This was a descriptive, prospective, and observational study with a cross sectional design. There were 30 menopausal women obtained by using purposive sampling method. Lipid profile was examined at Prodia Laboratorium Manado. Data were analyzed by using SPSS 20. The results showed that most respondents (86.7%) were ?65 years old. There were 21 women (70%) with total cholesterol level >200 mg/dl (mean value of 211.2 mg/dl); 27 women (90%) with LDL-cholesterol level >100 mg/dl (mean value of 137.8 mg/dl); 25 women (83.3%) with HDL cholesterol >40 mg/dl (mean value of 50.9 mg/dl); and 26 women (87.7%) with triglyceride level <150 mg/dl (mean value of 111.4 mg/dl). Conclusion: Most of the menopausal women at Panti Werdha Damai Manado were at the age of ?65 years. The average values of total and LDL cholesterol were above the reference value, meanwhile the average values of HDL cholesterol and triglycerides were within normal limit. Keywords: menopausal women, lipid profile. Abstrak: Di Indonesia perempuan yang berusia lebih dari 50 tahun telah memasuki menopause pada tahun 2020 diperkirakan sebanyak 30,3 juta orang. Saat menopause terjadi penurunan estrogen yang tidak hanya memengaruhi fungsi sistem reproduksi wanita, tetapi juga terhadap sistem tubuh lainnya antara lain metabolisme lipid. Penelitian ini bertujuan untuk mengetahui profil lipid wanita menopause di Panti Werdha Damai Manado. Jenis penelitian ialah observasional serta deskriptif prospektif dengan desain potong lintang. Didapatkan 30 wanita menopause dengan menggunakan metode purposive sampling dan dilakukan pemeriksaan profil lipid di Laboratorium Prodia Manado. Data dianalisis menggunakan SPSS 20. Hasil penelitian memperlihatkan bahwa sebagian besar responden (86,7%) berusia ?65 tahun. Kadar kolesterol total terbanyak ialah >200 mg/dl berjumlah 21 orang (70%) dengan nilai rerata 211,2 mg/dl. Kadar kolesterol LDL terbanyak ialah >100 mg/dl pada 27 orang (90%), nilai rerata 137,8 mg/dl. Kadar kolesterol HDL terbanyak ialah >40 mg/dl pada 25 orang (83,3%), nilai rerata 50,9 mg/dl. Kadar trigliserida terbanyak ialah <150 mg/dl pada 26 orang (86,7%), nilai rerata 111,4 mg/dl. Simpulan: Sebagian besar wanita menopause di Panti Werdha Damai Manado berusia ?65 tahun dengan nilai rerata kolesterol total dan kolesterol LDL berada di atas nilai rujukan sedangkan nilai rerata kolesterol HDL dan trigliserida sesuai nilai rujukan.Kata kunci: wanita menopause, profil lipid